Short Term Treatment Monitoring of Renal and Inflammatory Biomarkers with Naturally Occurring Leishmaniosis: A Cohort Study of 30 Dogs - Valeria Pantaleo; Tommaso Furlanello; Michela Campigli; Laura Ventura; Laia Solano-Gallego (Veterinary Sciences)
Various inflammatory and renal biomarkers have already been assessed for monitoring the response to anti-leishmanial therapy in canine leishmaniosis. This study assessed the parasite load, various inflammatory and renal biomarkers pre- and post-treatment, and any association between the studied variables and the degree of disease severity at diagnosis. This is a prospective cohort study of 30 client-owned dogs with leishmaniosis, classified according to LeishVet’s guidelines as stage I (n = 2), stage IIa (n = 7), stage IIb (n = 6), stage III (n = 8), and stage IV (n = 7). In addition to Leishmania real-time PCR in the bone marrow, blood and urine, previously studied biomarkers, and several inflammatory and renal markers never investigated in canine leishmaniosis, such as fibrinogen, antithrombin, urinary fractional excretion of sodium, and urinary amylase-to-creatinine ratio were measured pre- and post-treatment (meglumine antimoniate or miltefosine + allopurinol). A positive Leishmania real-time PCR in the blood at diagnosis predicted a positive Leishmania real-time PCR in the bone marrow post-treatment (p = 0.003). Following treatment, antithrombin and urinary amylase-to-creatinine ratio were significantly changed (p < 0.001, respectively). Urinary amylase-to-creatinine ratio, total iron-binding capacity, and antithrombin were the variables most strongly associated with disease severity (p < 0.005, respectively). Urinary amylase-to-creatinine ratio can be a useful marker to monitor treatment response and to classify the degree of disease severity.